Graphene / heterocyclic aramid composite fiber and preparation method thereof

By dispersing graphene in the spinning solution and adding a polymerization system before the polymerization reaction, the problem of graphene agglomeration in heterocyclic aramid fibers is solved, the mechanical properties and stability of the composite fibers are improved, and it is suitable for actual production.

CN119710962APending Publication Date: 2025-03-28BEIJING GRAPHENE INST +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311277802.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When graphene is introduced into heterocyclic aramid fibers, graphene agglomeration is easily caused, resulting in uneven spinning, poor stability and mechanical properties, and difficult to be used in actual production.

Method used

The graphene dispersion was prepared by first dispersing graphene in N,N’-dimethylacetamide solvent, and the graphene dispersion was added to the polymerization system before the polymerization reaction occurred to form a graphene polymerization liquid, and graphene/heterocyclic aramid composite fiber was prepared by wet spinning.

Benefits of technology

It improves the dispersion of graphene in the spinning solution, improves the mechanical properties and stability of composite fibers, solves the problem of graphene agglomeration, and is suitable for actual production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710962A_ABST
    Figure CN119710962A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene / heterocyclic aramid composite fiber and a preparation method thereof. Small-size graphene is used as an initial raw material, no additive (such as lithium chloride or calcium chloride) is added in the preparation process of the graphene dispersion liquid, and the graphene dispersion liquid is added into a polymerization reaction system before polymerization reaction, so that the mechanical property of the composite fiber is improved. Compared with a technical scheme without adding graphene, the mechanical stability of the graphene-based composite material is improved under natural conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon materials, and specifically relates to a graphene / heterocyclic aramid composite fiber and a preparation method thereof. Background Art

[0002] Heteroaramid fiber is an organic high-performance fiber with excellent properties such as light weight, high strength, high modulus, and impact resistance. It has important applications in aerospace and defense industries such as engine casings of weapon systems, bulletproof helmets, and aircraft skins. In engineering applications, domestic heteroaramid fibers still face a large gap in mechanical properties compared to foreign ones, and their use areas are relatively limited. Therefore, how to develop a series of fiber products based on the structural weaknesses of heteroaramid fibers and the needs of actual application scenarios is the key to realizing the application of heteroaramid fibers. Graphene is composed of sp 2 Two-dimensional nanocarbon materials composed of hybrid carbon atoms arranged in a honeycomb-like structure have the characteristics of high strength, high modulus and high specific surface area, and are ideal structural reinforcement materials.

[0003] At present, some studies have introduced graphene into heterocyclic aramid fibers. For example, in Chinese invention patent CN202110977053.9, graphene materials are added to aramid resin solutions as graphene aramid spinning solutions; however, direct mixing easily causes graphene agglomeration, making the aramid fibers obtained by spinning uneven, with poor stability and mechanical properties, making them difficult to use in actual production. Summary of the invention

[0004] Compared with the method of directly adding graphene powder to the polymerization solution, the method of first dispersing graphene in N,N'-dimethylacetamide solvent to obtain a graphene dispersion can greatly improve the dispersibility of graphene in the spinning solution (such as in Chinese invention patent CN202110419613.9, graphene is dissolved in N,N'-dimethylacetamide / lithium chloride composite solvent to obtain a graphene dispersion, and then aramid monomers p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, and terephthaloyl chloride are added to the graphene dispersion to obtain a graphene aramid spinning solution). The inventors further found that the above method has the problem of easily causing graphene agglomeration; therefore, the graphene dispersion cannot be stored for a long time, and is only suitable for the preparation of spinning solution immediately after preparation, which brings many inconveniences to actual production. In addition, dissolving p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in a dispersion of graphene will also have an adverse effect on the dispersibility of graphene.

[0005] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a graphene / heterocyclic aramid composite fiber, which specifically comprises the following steps:

[0006] (1) Preparation of graphene dispersion: adding graphene material into N,N-dimethylacetamide solvent to prepare graphene dispersion;

[0007] (2) Preparation of graphene polymerization liquid: before the polymerization reaction occurs, adding the above graphene dispersion liquid into the polymerization reaction system to form a graphene polymerization liquid;

[0008] (3) The graphene / heterocyclic aramid composite fiber is prepared by wet spinning.

[0009] According to a specific embodiment of the present invention, the graphene material is graphene powder, which can effectively improve the mechanical stability of the composite fiber compared to graphene oxide.

[0010] According to a specific embodiment of the present invention, the sheet diameter of the graphene material is 0.01-0.3 μm.

[0011] According to a specific embodiment of the present invention, the carbon-oxygen ratio of the graphene material is ≥5, and the number of layers is 1 to 10; preferably, the carbon-oxygen ratio of the graphene material is ≥10, and the number of layers is 1 to 5.

[0012] According to a specific embodiment of the present invention, the graphene dispersion further contains a surfactant; preferably, the surfactant is polyvinyl pyrrolidone.

[0013] Wherein, the ratio of the added amount of polyvinyl pyrrolidone to the mass of graphene is (1-3):1.

[0014] According to a specific embodiment of the present invention, step (2) specifically includes the following steps: adding LiCl, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole to a reaction kettle containing N,N'-dimethylacetamide, and stirring under nitrogen until completely dissolved; adding the above-mentioned graphene dispersion after cooling, stirring, adding terephthaloyl chloride in batches, and stirring thoroughly to obtain a graphene / heterocyclic aramid polymerization solution.

[0015] According to a specific embodiment of the present invention, the above-mentioned cooling step specifically includes: lowering the temperature to -10 to 10°C.

[0016] According to a specific embodiment of the present invention, the stirring time after adding the graphene dispersion is 5 to 20 minutes; and / or, the sufficient stirring time is 5 to 8 hours.

[0017] According to a specific embodiment of the present invention, the step (3) specifically includes the following steps: the above-mentioned graphene / heterocyclic aramid polymer solution is subjected to a spinning process to obtain the primary fibers of heterocyclic aramid containing graphene, and then subjected to a secondary coagulation bath, water washing, drying, and heat stretching treatment at 370-420°C under a nitrogen atmosphere, and finally rolled into graphene / heterocyclic aramid composite fibers.

[0018] According to a specific embodiment of the present invention, the method for preparing nascent fibers includes: vacuum degassing the graphene / heterocyclic aramid polymer solution, and then evenly spraying it out from a spinneret, and then performing double diffusion and a certain stretching action in a primary coagulation bath to form nascent fibers.

[0019] According to a specific embodiment of the present invention, the mass percentage of graphene material in the graphene / heterocyclic aramid composite fiber is 0.01% to 1%, preferably 0.01% to 0.5%.

[0020] The second object of the present invention is to provide graphene / heterocyclic aramid composite fibers prepared by the above preparation method.

[0021] Beneficial Effects

[0022] The present invention uses small-sized graphene as the initial raw material, does not add any additives (such as lithium chloride or calcium chloride) during the preparation of the graphene dispersion, and adds the graphene dispersion into the polymerization reaction system before the polymerization reaction occurs, thereby improving the mechanical properties of the composite fiber. Compared with the technical solutions of adding graphene oxide and not adding graphene under natural conditions, its mechanical stability is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a photo of the graphene / heterocyclic aramid composite fiber prepared in Example 1;

[0024] Figure 2 The SEM images of the graphene in Example 1 and the graphene in Comparative Example 2 are shown.

[0025] Figure 3 The photos of the spinning screens in Example 1 and Comparative Example 2 are shown;

[0026] Figure 4 The force-displacement curves of the mechanical properties test of the composite fibers of Example 1 and Comparative Example 2;

[0027] Figure 5 These are photos of the composite fibers prepared in Example 1 and the comparative example dissolved in DMSO / KOH. DETAILED DESCRIPTION

[0028] The following further exemplifies the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0029] The preparation method of the graphene / heterocyclic aramid composite fiber of the present invention specifically comprises: (1) preparing a graphene dispersion liquid: adding a graphene material into an N,N-dimethylacetamide solvent to prepare a graphene dispersion liquid; (2) preparing a graphene polymer liquid: before a polymerization reaction occurs, adding the graphene dispersion liquid into a polymerization reaction system to form a graphene polymer liquid; and (3) preparing the graphene / heterocyclic aramid composite fiber by wet spinning.

[0030] Step (1) is specifically as follows: taking a small-sized graphene powder or a small-sized reduced graphene oxide (hereinafter referred to as graphene) accounting for 0.01 to 1% of the mass fraction of the polymer and drying it in a 100° C. oven for 8 hours. Then taking out the graphene powder, adding it to an organic solvent of N, N-dimethylacetamide (DMAC, 300 mL) containing a polyvinyl pyrrolidone surfactant and ultrasonically dispersing it for 30 to 60 minutes to obtain a uniform and stable graphene dispersion.

[0031] The present invention does not add any cosolvent (lithium chloride or calcium chloride) to the composite dispersion of graphene / N,N'-dimethylacetamide, but only adds dispersants such as polyvinyl pyrrolidone. The advantage of this method is that graphene is not easy to agglomerate in the composite solvent and is easy to store.

[0032] The graphene powder has a carbon-oxygen ratio of ≥5, a number of layers of 1 to 10, and a sheet diameter of 0.01 to 0.3 μm. Preferably, the graphene has a carbon-oxygen ratio of ≥10 and a number of layers of 1 to 5.

[0033] The use of small-sized graphene is beneficial to improving the dispersion of graphene and making it less likely to agglomerate. Compared with large-sized graphene, it helps to improve the mechanical properties of the target product, graphene / heterocyclic aramid composite fiber.

[0034] In addition, in the technical solution of the present invention, graphene powder or reduced graphene oxide powder is used as raw material, and the mechanical stability of the prepared aramid fiber and aramid blank fiber is better than that of graphene oxide.

[0035] Step (2) is specifically as follows: add cosolvent LiCl, p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and other polymerization monomers into a reaction kettle filled with N,N'-dimethylacetamide, and stir under nitrogen until completely dissolved. After the temperature is lowered to -10 to 10°C, the graphene dispersion prepared above is added to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stirred. The stirring time is 5 to 20 minutes, and terephthaloyl chloride is added in batches, and stirred for 5 to 8 hours to obtain a polymerization solution of graphene / heterocyclic aramid.

[0036] Before the polymerization reaction occurs, the graphene dispersion is added into a mixed solvent in which 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are completely dissolved in advance, and terephthaloyl chloride is added in batches after stirring for 5 to 20 minutes. The advantages are: first, compared with directly adding the undissolved 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine to the graphene dispersion, the above-mentioned addition sequence can effectively avoid the graphene agglomeration caused by the solid and highly sticky 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine; secondly, adding the graphene dispersion to the pre-dissolved 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine / N,N'-dimethylacetamide mixed solvent can reduce the stirring time of the graphene in the reactor, so that the graphene can be well dispersed in the composite solvent without agglomeration; in addition, the graphene is added before the terephthaloyl chloride to participate in the polymerization process of the aramid monomer, so that the graphene can be well dispersed in the polymer without agglomeration.

[0037] Step (3) is specifically as follows: vacuum degassing the graphene / heterocyclic aramid polymer solution, and then evenly spraying it out from the spinneret, passing through a primary coagulation bath for double diffusion and a certain stretching action to form primary fibers, and then passing through a secondary coagulation bath, washing, and drying, and then entering a temperature of 370 to 420° C. and a nitrogen atmosphere for heat stretching treatment, and finally winding it into a graphene / heterocyclic aramid composite fiber.

[0038] In the technical solution of the invention, the mass content of graphene in the graphene / heterocyclic aramid composite fiber is controlled to be 0.01% to 1% of the fiber matrix, preferably 0.01% to 0.5%. For example, the content can be 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%.

[0039] If the amount of graphene added exceeds a certain limit, the dispersibility of the graphene in the composite polymer solution will decrease, which will lead to unbalanced mechanical properties of the composite fiber. The present invention controls the amount of graphene within the above range to facilitate uniform dispersion of the graphene in the polymer.

[0040] Example 1

[0041] (1) Preparation of graphene dispersion:

[0042] Take 0.1g of graphene powder (carbon-oxygen ratio of 10.25, number of layers of 2 to 5 layers, and flake diameter of 30 to 50nm) and put it into a 100°C oven for drying for 8 hours. Then take out the graphene powder and add it to an organic solvent of N, N-dimethylacetamide (DMAC, 300g) containing polyvinyl pyrrolidone (PVP content of 0.2g) for ultrasonic dispersion for 30 to 60 minutes to obtain a graphene dispersion.

[0043] (2) Preparation of graphene polymer solution:

[0044] Add 128.76g LiCl, 23.35g p-phenylenediamine, and 90.46g 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing 4657.92g N,N'-dimethylacetamide, and stir under nitrogen until completely dissolved. After the temperature is reduced to 5°C, add the above-prepared graphene dispersion to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stir for 15 minutes. Add terephthaloyl chloride in 2 batches, adding 121.5g and 1.4g respectively, and stir thoroughly for 5 hours to obtain a graphene / heterocyclic aramid polymerization solution.

[0045] (3) Preparation of graphene / heterocyclic aramid composite fibers:

[0046] The graphene / heterocyclic aramid polymer solution is vacuum degassed, and then uniformly ejected from the spinneret, and then subjected to double diffusion and a certain stretching action in a primary coagulation bath to form primary fibers, and then subjected to a secondary coagulation bath, water washing, and drying, and then subjected to heat stretching treatment in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into graphene / heterocyclic aramid composite fibers, such as Figure 1 As shown. The breaking strength of the composite fiber is 35.99 cN / dtex, the breaking elongation is 3.87%, and the elastic modulus is 959.89 cN / dtex. The composite fiber is stored at room temperature and away from light. After 6 months, the mechanical properties of the fiber are still stable, and the re-measured breaking strength is 36.02 cN / dtex, the breaking elongation is 3.82%, and the elastic modulus is 968.54 cN / dtex.

[0047] Example 2

[0048] Other parameters and steps are the same as those in Example 1, except that the flake diameter of the graphene powder is 20-30 nm.

[0049] (1) Preparation of graphene dispersion:

[0050] Take 0.1g of graphene powder (carbon-oxygen ratio of 10.08, number of layers of 2 to 5 layers, and flake diameter of 20 to 30nm) and put it into a 100°C oven for drying for 8 hours. Then take out the graphene powder and add it to an organic solvent of N, N-dimethylacetamide (DMAC, 300g) containing polyvinyl pyrrolidone (PVP content of 0.2g) for ultrasonic dispersion for 30 to 60 minutes to obtain a graphene dispersion.

[0051] (2) Preparation of graphene polymer solution:

[0052] Add 128.76g LiCl, 23.35g p-phenylenediamine, and 90.46g 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing 4657.92g N,N'-dimethylacetamide, and stir under nitrogen until completely dissolved. After the temperature is reduced to 5°C, add the above-prepared graphene dispersion to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stir for 15 minutes. Add terephthaloyl chloride in 2 batches, adding 121.5g and 1.4g respectively, and stir thoroughly for 5 hours to obtain a graphene / heterocyclic aramid polymerization solution.

[0053] (3) Preparation of graphene / heterocyclic aramid composite fibers:

[0054] The graphene / heterocyclic aramid polymer solution is vacuum degassed, and then uniformly ejected from the spinneret, and then double diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into graphene / heterocyclic aramid composite fibers. The composite fiber has a breaking strength of 36.19 cN / dtex, a breaking elongation of 3.85%, and an elastic modulus of 976.43 cN / dtex.

[0055] Example 3

[0056] (1) Preparation of graphene dispersion:

[0057] Take 0.1g of graphene powder (carbon-oxygen ratio of 9.68, number of layers of 2 to 5, and flake diameter of 80 to 100nm) and put it into a 100°C oven for drying for 8 hours. Then take out the graphene powder and add it to an organic solvent of N, N-dimethylacetamide (DMAC, 300g) containing polyvinyl pyrrolidone (PVP content of 0.2g) for ultrasonic dispersion for 30 to 60 minutes to obtain a graphene dispersion.

[0058] (2) Preparation of graphene polymer solution:

[0059] Add 128.76g LiCl, 23.35g p-phenylenediamine, and 90.46g 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing 4657.92g N,N'-dimethylacetamide, and stir under nitrogen until completely dissolved. After the temperature is reduced to 5°C, add the above-prepared graphene dispersion to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stir for 15 minutes. Add terephthaloyl chloride in 2 batches, adding 121.5g and 1.4g respectively, and stir thoroughly for 5 hours to obtain a graphene / heterocyclic aramid polymerization solution.

[0060] (3) Preparation of graphene / heterocyclic aramid composite fibers:

[0061] The graphene / heterocyclic aramid polymer solution is vacuum degassed, and then uniformly ejected from the spinneret, and then double diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into graphene / heterocyclic aramid composite fibers. The composite fiber has a breaking strength of 35.74 cN / dtex, a breaking elongation of 3.77%, and an elastic modulus of 934.74 cN / dtex.

[0062] Comparative Example 1

[0063] Other parameters and steps are the same as those in Example 1, except that the initial raw materials are Graphene oxide .

[0064] (1) Preparation of graphene oxide dispersion:

[0065] 0.1 g of graphene oxide powder (carbon-oxygen ratio of 2.3, number of layers of 6, flake diameter of 800 nm) was placed in a 100°C oven and dried for 8 hours. The graphene oxide powder was then taken out and added to an organic solvent of N, N-dimethylacetamide (DMAC, 300 g) containing polyvinyl pyrrolidone (PVP content of 0.2 g) for ultrasonic dispersion for 30 to 60 minutes to obtain a graphene oxide dispersion.

[0066] (2) Preparation of graphene oxide polymer solution:

[0067] Add 128.76g LiCl, 23.35g p-phenylenediamine, and 90.46g 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing 4657.92g N,N'-dimethylacetamide, and stir under nitrogen until completely dissolved. After the temperature is reduced to 5°C, the graphene oxide dispersion prepared above is added to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stirred for 15 minutes. Add terephthaloyl chloride in 2 batches, adding 121.5g and 1.4g respectively, and stir thoroughly for 5h to obtain a polymerization solution of graphene oxide / heterocyclic aramid.

[0068] (3) Preparation of graphene oxide / heterocyclic aramid composite fibers:

[0069] The graphene oxide / heterocyclic aramid polymer solution is vacuum degassed, and then uniformly ejected from the spinneret, and then double diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into graphene oxide / heterocyclic aramid composite fibers. The composite fiber has a breaking strength of 35.34 cN / dtex, an elongation at break of 3.67%, and an elastic modulus of 875 cN / dtex. The composite fiber is stored at room temperature and away from light. After 6 months, the mechanical properties of the fiber have decreased, and the re-measured breaking strength is 34.53 cN / dtex, the elongation at break is 3.58%, and the elastic modulus is 862 cN / dtex.

[0070] Comparative Example 2

[0071] Other parameters and steps are the same as those in Example 1, except that the graphene particle size has a carbon-oxygen ratio of 5.6, the number of layers is 8 to 10, and the sheet diameter is 0.8 to 1 μm.

[0072] (1) Preparation of graphene dispersion:

[0073] Take 0.1 reduced graphene oxide powder (carbon-oxygen ratio of 5.6, number of layers of 8 to 10 layers, and sheet diameter of 0.8 to 1 μm) and put it into a 100°C oven for drying for 8 hours. Then take out the graphene powder and add it to an organic solvent of N, N-dimethylacetamide (DMAC, 300 g) containing polyvinyl pyrrolidone (PVP content of 0.2 g) for ultrasonic dispersion for 30 to 60 minutes to obtain a graphene dispersion.

[0074] (2) Preparation of graphene polymer solution:

[0075] Add 128.76g LiCl, 23.35g p-phenylenediamine, and 90.46g 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing N,N'-dimethylacetamide (4657.92g), and stir under nitrogen until completely dissolved. After the temperature is reduced to 5°C, add the above-prepared graphene dispersion to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stir for 15 minutes. Add terephthaloyl chloride in 2 batches, adding 121.5g and 1.4g respectively, and stir thoroughly for 5h to obtain a graphene / heterocyclic aramid polymerization solution.

[0076] (3) Preparation of graphene / heterocyclic aramid composite fibers:

[0077] The graphene / heterocyclic aramid polymer solution is vacuum degassed, and then uniformly ejected from the spinneret, and then double diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into graphene / heterocyclic aramid composite fibers. The mechanical properties of the composite fiber are relatively low, with a breaking strength of 33.24 cN / dtex, a breaking elongation of 3.52%, and an elastic modulus of 837 cN / dtex.

[0078] Figure 2 The SEM images of the graphene in Example 1 (left) and the graphene in Comparative Example 2 (right) are shown. As can be seen from the figure, the graphene particles in the left figure are graphene with a sheet diameter of 30 to 50 nm, and the graphene particles in the right figure are graphene with a sheet diameter of 0.5 to 1 micrometer.

[0079] Figure 3 These are photos of the spinning filter (a) in Example 1 and the spinning filter (b) in Comparative Example 2; as can be seen from the figures, the spinning filter of Example 1 on the left is not clogged, indicating that the graphene is well dispersed, and the spinning filter of Comparative Example 2 on the right is severely clogged, indicating that the graphene dispersion is very poor.

[0080] Figure 4 Force-displacement curves of mechanical property tests of composite fibers of Example 1 (left) and Comparative Example 2 (right). It can be seen that the composite fibers prepared in Example 1 have higher breaking strength.

[0081] Comparative Example 3

[0082] The other parameters and steps are the same as those in Example 1, except that lithium chloride is added when preparing the graphene dispersion in step (1).

[0083] (1) Preparation of graphene dispersion:

[0084] 0.1 g of graphene powder (carbon-oxygen ratio of 9.8, number of layers of 2 to 5, and sheet diameter of 30 to 50 nm) was placed in a 100° C. oven and dried for 8 hours. The graphene powder was then taken out and added to an organic solvent of N, N-dimethylacetamide (DMAC, 300 g) containing polyvinyl pyrrolidone (PVP content of 0.2 g) and lithium chloride (LiCl content of 10 g) for ultrasonic dispersion for 30 to 60 minutes to obtain a graphene dispersion.

[0085] (2) Preparation of graphene polymer solution:

[0086] Add 128.76g LiCl, 23.35g p-phenylenediamine, and 90.46g 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing N,N'-dimethylacetamide (4657.92g), and stir under nitrogen until completely dissolved. After the temperature is reduced to 5°C, add the above-prepared graphene dispersion to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stir for 15 minutes. Add terephthaloyl chloride in 2 batches, adding 121.5g and 1.4g respectively, and stir thoroughly for 5h to obtain a graphene / heterocyclic aramid polymerization solution.

[0087] (3) Preparation of graphene / heterocyclic aramid composite fibers:

[0088] The graphene / heterocyclic aramid polymer solution is vacuum degassed, and then uniformly ejected from the spinneret, and then double diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into graphene / heterocyclic aramid composite fibers. The composite fiber has a breaking strength of 32.4 cN / dtex, a breaking elongation of 3.37%, and an elastic modulus of 829 cN / dtex.

[0089] Comparative Example 4

[0090] The other parameters and steps are the same as those in Example 1, except that in step (2), LiCl, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole that are not pre-dissolved are directly added to the graphene dispersion.

[0091] (1) Preparation of graphene dispersion:

[0092] Take 0.1g of graphene powder (carbon-oxygen ratio of 9.8, number of layers of 2 to 5 layers, and flake diameter of 30 to 50nm) and put it into a 100°C oven for drying for 8 hours. Then take out the graphene powder and add it to an organic solvent of N, N-dimethylacetamide (DMAC, 300g) containing polyvinyl pyrrolidone (PVP content of 0.2g) for ultrasonic dispersion for 30 to 60 minutes to obtain a graphene dispersion.

[0093] (2) Preparation of graphene polymer solution:

[0094] The graphene dispersion in step (1) was added to a reactor containing N,N'-dimethylacetamide (4657.92 g), and stirred under nitrogen for 15 minutes until completely mixed. 128.76 g of LiCl, 23.35 g of p-phenylenediamine, and 90.46 g of 2-(4-aminophenyl)-5-aminobenzimidazole that were not pre-dissolved were directly added to the above graphene mixed solution and stirred until completely dissolved, and then the temperature was lowered to 5°C and terephthaloyl chloride was added in two batches, 121.5 g and 1.4 g respectively, and stirred for 5 hours to obtain a graphene / heterocyclic aramid polymerization solution.

[0095] (3) Preparation of graphene / heterocyclic aramid composite fibers:

[0096] The graphene / heterocyclic aramid polymer solution is vacuum degassed, and then uniformly ejected from the spinneret, and then double diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into graphene / heterocyclic aramid composite fibers. The mechanical properties of the composite fiber are relatively low, with a breaking strength of 30.57 cN / dtex, a breaking elongation of 3.21%, and an elastic modulus of 813 cN / dtex.

[0097] Comparative Example 5

[0098] The other parameters and steps are the same as those in Example 1, except that graphene is not added.

[0099] (1) Preparation of heterocyclic aramid polymer solution:

[0100] Add 128.76g LiCl, 23.35g p-phenylenediamine, and 90.46g 2-(4-aminophenyl)-5-aminobenzimidazole to a reactor containing N,N'-dimethylacetamide (4957.92g), and stir under nitrogen until completely dissolved. After the temperature is reduced to 5°C, the graphene dispersion prepared above is added to the mixed solvent in which the above monomers have been completely dissolved before the polymerization reaction occurs and stirred for 15 minutes. Add terephthaloyl chloride in 2 batches, adding 121.5g and 1.4g respectively, and stir thoroughly for 5h to obtain a graphene / heterocyclic aramid polymerization solution.

[0101] (2) Preparation of heterocyclic aramid composite fibers:

[0102] The heterocyclic aramid polymer solution is vacuum degassed, and then uniformly sprayed out from the spinneret, and then double-diffused and stretched in a primary coagulation bath to form primary fibers, and then passed through a secondary coagulation bath, washed with water, dried, and then heat stretched in a nitrogen atmosphere at a temperature of 400°C, and finally rolled into heterocyclic aramid composite fibers. The fiber has a breaking strength of 33.88 cN / dtex, a breaking elongation of 3.61%, and an elastic modulus of 909.09 cN / dtex. The fiber is stored at room temperature and away from light. After 6 months, the mechanical properties of the fiber decrease slightly, and its re-measured breaking strength is 33.24 cN / dtex, the breaking elongation is 3.46%, and the elastic modulus is 898 cN / dtex.

[0103] Figure 5 The dissolution state of the composite fibers prepared in Example 1 (left) and Comparative Example 5 (right) placed in a mixed solution of DMSO / KOH for 30 minutes. It can be seen from the figure that the graphene composite fiber is almost not dissolved, the fiber remains intact, and the fiber without graphene is completely dissolved. It can be seen that the graphene composite fiber obtained by the technical solution of the present application has better stability in DMSO.

[0104] The mechanical test results of Examples 1-3 and Comparative Examples 1-5 are summarized in Table 1:

[0105] Table 1

[0106]

[0107] It can be seen from the data of Comparative Examples 1, 5 and Example 1 that the mechanical properties of the composite fiber obtained by using graphene as the initial raw material are significantly improved compared with graphene oxide or without adding graphene; it can be seen from the data of Comparative Example 2 and Example 1 that the mechanical properties of the composite fiber obtained by using small-sized graphene are greatly improved compared with large-sized graphene; it can be seen from the data of Comparative Example 3 and Example 1 that when preparing the graphene dispersion, no auxiliary agents such as lithium chloride are added, and the mechanical properties of the obtained composite fiber are better; it can be seen from the data of Comparative Example 4 and Example 1 that the addition order of the present application (i.e., adding the graphene dispersion to the polymerization reaction system before the polymerization reaction occurs) can improve the mechanical properties of the composite fiber.

[0108] In addition, it can be seen from the test data of Comparative Examples 1, 5 and Example 1 after 6 months that the composite fiber obtained by adopting the technical solution of the present application has better mechanical stability.

[0109] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0110] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.

Claims

1. A method for preparing a graphene / heterocyclic aramid composite fiber, characterized in that: The specific steps include: (1) Preparation of graphene dispersion: adding graphene material into N,N-dimethylacetamide solvent to prepare graphene dispersion; (2) Preparation of graphene polymerization liquid: before the polymerization reaction occurs, adding the graphene dispersion liquid into the polymerization reaction system to form a graphene polymerization liquid; (3) The graphene / heterocyclic aramid composite fiber is prepared by wet spinning.

2. The preparation method according to claim 1, characterized in that: The graphene material is graphene powder.

3. The preparation method according to claim 1, characterized in that: The sheet diameter of the graphene material is 0.01-0.3 μm.

4. The preparation method according to claim 1, characterized in that: The carbon-oxygen ratio of the graphene material is ≥5, and the number of layers is 1 to 10; preferably, the carbon-oxygen ratio of the graphene material is ≥10, and the number of layers is 1 to 5.

5. The preparation method according to claim 1, characterized in that: The graphene dispersion further contains a surfactant; preferably, the surfactant is polyvinyl pyrrolidone.

6. The preparation method according to claim 1, characterized in that: Step (2) specifically includes the following steps: adding LiCl, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole to a reaction kettle containing N,N'-dimethylacetamide, and stirring under nitrogen until completely dissolved; adding the graphene dispersion after cooling, stirring, adding terephthaloyl chloride in batches, and stirring thoroughly to obtain a graphene / heterocyclic aramid polymerization solution.

7. The preparation method according to claim 6, characterized in that: The cooling step specifically includes: lowering the temperature to -10 to 10°C.

8. The preparation method according to claim 1, characterized in that: The step (3) specifically includes the following steps: subjecting the graphene / heterocyclic aramid polymer solution to a spinning process to obtain primary fibers of heterocyclic aramid containing graphene, and then subjecting the fibers to a secondary coagulation bath, water washing, and drying, and subjecting the fibers to a heat stretching treatment at 370 to 420° C. in a nitrogen atmosphere, and finally winding the fibers into graphene / heterocyclic aramid composite fibers.

9. The preparation method according to claim 1, characterized in that: The mass percentage of the graphene material to the graphene / heterocyclic aramid composite fiber is 0.01% to 1%, preferably 0.01% to 0.5%.

10. The graphene / heterocyclic aramid composite fiber prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Graphene high-strength impact-resistant aramid fiber and preparation method thereof

    CN113718364A

  • A method for preparing graphene-modified high-strength, high-modulus heterocyclic aramid fibers

    CN115216857B

  • Polyvinyl pyrrolidone / graphene conductive slurry, and preparation method and application thereof

    CN105552376A

  • Graphene dispersion liquid and preparation method thereof

    CN111232966A

  • Olefinic carbon material dispersion liquid and application thereof

    CN113248739A